How is Technology Positioned in the Implementation of SSI-Based Learning? - Ariyati, Eka; Yokhebed, Yokhebed; Marlina, Reni (FKIP Universitas Lampung, 2025)
How is Technology Positioned in the Implementation of SSI-Based Learning? Objectives: Socio-Scientific Issues (SSI)-based learning is an educational approach that combines scientific content with ethical, social, and real-world issues. This learning model is significantly influenced by technology, which enhances student engagement, facilitates access to a variety of information sources, and offers interactive and immersive experiences. This research endeavors to conduct a comprehensive analysis of the position of technology in SSI-based learning, with a particular emphasis on its functions, forms of application, and effects. Methods: The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) method was employed to conduct the Systematic Literature Review (SLR). Keywords associated with